Penerapan Konsep Fisika Dalam Praktek Pemasangan Tulangan Balok Dan Kolom Di Lapas Kelas 2B Nunukan - Rahmawati, Lusy; Syarif, Muhammad; Yoseph, Yoseph; Astika, Sri; Anggini, Canda Putri (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
The community service was aimed at improving theoretical understanding and practical skill on construction of the prisoners in Nunukan Class 2B Prison. The material in the workshop included introduction to the principles of Physiscs relevant to beam and column installation, healthy house concept, and earthquake-resistant simple house design. The workshop was carried out using participatory approach in which participants actively contributed on the discussion, simulation, and application. This approach was selected as it increases togetherness and solidarity among participants. The result indicated that there was a significant improvement on participants’ technical skill, especially in the application of reinforcement installation standards. In addition, the workshop succeeded in strengthening solidarity and cooperation among prisoners through group work. Moreover, the documentation of the activity revealed the success of the program although the time was limited.  In conclusion, the workshop provided a positive impact, both in the short and long term. The prisoners could increase their technical skills and their skills can be applied in the future. This activity also has the potential to be replicated in other places with some adaptation according to the local needs.